Submesoscale Impacts on Mesoscale Agulhas Dynamics - R. Schubert; F. U. Schwarzkopf; B. Baschek; A. Biastoch (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Mesoscale dynamics of the Agulhas Current system determine the exchange between the Indian and Atlantic oceans, thereby influencing the global overturning circulation. Using a series of ocean model experiments compared to observations, we show that the representation of mesoscale eddies in the Agulhas ring path improves with increasing resolution of submesoscale flows. Simulated submesoscale dynamics are validated with time‐mean horizontal‐wavenumber spectra from satellite sea surface temperature measurements and mesoscale dynamics with spectra from sea surface height. While the Agulhas ring path in a nonsubmesoscale‐resolving (1/20)° configuration is associated with too less power spectral densities on all scales and too steep spectral slopes, the representation of the mesoscale dynamics improves when the diffusion and the dissipation of the model are reduced and some small‐scale features are resolved. Realistic power spectral densities over all scales are achieved when additionally the horizontal resolution is increased to (1/60)° and a larger portion of the submesoscale spectrum is resolved. Results of an eddy detection algorithm applied to the model outputs as well as to a gridded sea surface height satellite product show that in particular strong cyclones are much better represented when submesoscale flows are resolved by the model. The validation of the submesoscale dynamics with sea surface temperature spectra provides guidance for the choice of advection schemes and explicit diffusion and dissipation as well as for further subgrid‐scale parameterizations. For the Agulhas ring path, the use of upstream biased advection schemes without explicit diffusion and dissipation is found to be associated with realistically simulated submesoscales.